Examination of the different medicine effects at MDAH-2774 human ovary cancer three dimensional cell culture with nitric oxide synthase changing - Ayla, Şule; Öktem, Gülperi; Bilir, Ayhan (Cerrahpaşa Medical Journal, 2013)
Objectives: The purpose of our study is to examine the effects of the various medicines at the three dimensional MDAH-2774 human ovary cancer culture with cell proliferation and nitric oxide synthase changing. Methods: Using of medicines at the two dimensional cultures jointly or severally was examined by immunohystochemical method in terms of cell increasing at the 24th, 48th, 72nd and 96th hours and in terms of activities of excitable (inducible) nitric oxide synthase and endothelial nitric oxide synthase at the tree dimensional cultures. Results: Using of these medicines in Paracetamol, gemsitabine and Gemsitabine + Paracetamol and Gemsitabine + Resveratrol combination groups, reduced the number of the cells at all hours according to the control (p<0,05). When performed immunohystochemical analyses were individually compared with the cells of MDAH-2774 or medicine combination, it indicated that caused increasing at inducible nitric oxide synthase and endothelial nitric oxide synthase immunoreactivity. Immunoreactivity increased markedly at the 96th hour in comparison with the 24th hour. Conclusion: Using of the medicines one by one or in combination, reduced the cell proliferation at all hour time zones and increased inducible nitric oxide synthase and endothelial nitric oxide synthase activity.